Integrated-Software Sustainability Evaluation Model (i-SSEM) development - Ahmad, Ruzita; Hussain, Azham; Baharom, Fauziah (Universiti Teknikal Malaysia Melaka, 2018)
An integrated-Software Sustainability Evaluation Model (i-SSEM) presents the holistic evaluation criteria of software sustainability with performed the systematic measurement by using Goal Question Metric (GQM) approach. The required of the holistic evaluation in software sustainability is to address the limitations of the previous studies in which the needs to integrate all evaluation criterion into sustainability dimension such as environment, economic and social. The evaluation criteria are supported by references standards such as standard organization of product quality, sustainability development principal introduced by Bruntland Commission Report and the best practices from individual and organization in software sustainability evaluation (SSE). In order to provide the holistic SSE with integrated all sustainability dimensions, the proposed characteristic and sub-characteristic is evaluated based on “what, who, when, why, where” and “how” to measure the criteria. The proposed evaluation criteria consist nine (9) characteristics and thirty-two (32) sub-characteristics with nineteen (19) metrics. Embedded of GQM contributes in defining the measurement goals by determining the purposes, perspectives, point of views in the following context of environment with respect to achieve software sustainability.